A teoria da hegemonia de Ernesto Laclau e a análise política brasileira - Daniel de Mendonça (Ciências Sociais Unisinos)
The article has two main goals. First, it presents the most recent development of the notion of hegemony in Ernesto Laclaus political thought. Second, it tries to demonstrate the heuristic potential of this notion in political analysis, particularly of Brazilian politics. At the end the article discusses the explanatory potential of the notion of hegemony for two political moments of Brazils recent history: the Diretas já movement (1984) and the electoral victory, the illness and death of Tancredo Neves (1985).